Parameters observation of restoration capacity of industrial lead acid battery using high current pulses - N. S. M. Ibrahim; Asmarashid Ponniran; R. A. Rahman; M. P. Martin; A. Yassin; A. Eahambram; M. H. Aziz (Institute of Advanced Engineering and Science, 2020)
Batteries play an essential role on most of the electrical equipment and electrical engineering tools. However, one of the drawbacks of lead acid batteries is PbSO4 accumulates on the battery plates, which significantly cause deterioration. Therefore, this study discusses the discharge capacity performance evaluation of the industrial lead acid battery. The selective method to improve the discharge capacity is using high current pulses method. This method is performed to restore the capacity of lead acid batteries that use a maximum direct current (DC) of up to 500 A produces instantaneous heat from 27°C to 48°C to dissolve the PbSO4 on the plates. This study uses an 840 Ah, 36 V flooded lead acid batteries for a forklift for the evaluation test. Besides, this paper explores the behavior of critical formation parameters, such as the discharge capacity of the cells. From the experimental results, it can be concluded that the discharge capacity of the flooded lead acid battery can be increase by using high current pulses method. The comparative findings for the overall percentage of discharge capacity of the batteries improved from 68% to 99% after the restoration capacity.